A Comprehensive Survey on Emerging Trends in Networking and Communication : From IoT to Edge Computing - Ahmed Jumaa Lafta; Aya Falah Mahmood (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
The advancement of networking and communication technologies has escalated the IoT and edge computing integration by leaps and bounds. This paper provides a review of the current trends, technologies and issues concerning IoT and edge computing. Looking at the key application areas of smart cities, healthcare, industrial IoT and smart grids this paper demonstrates how edge computing solves the problems of cloud computing such as latency, bandwidth and privacy. The survey also reveals present day constraints such as the lack of standards for scalability, integration problems, and lack of strong data protection measures. This work can be considered as a reference source for researchers and practitioners since it reveals the relationship between IoT and edge computing and gives an idea of further advancements.